Cultural Dimension in the Educational Approach of Integral Prevention "Circle of Integral Well-Being." Reflections from the Discipline of Counseling - Artavia Aguilar, Cindy Vanessa (2022)
The changes, demands and social challenges, as well as the new scenarios in various areas of the human being lead us to reflect on and to review the models, approaches, strategies and designs in Counseling. The purpose of this research is to contribute to the scientific debate in this discipline and other areas that converge in the comprehensive care of the human being. Therefore, the intended objective is to propose the cultural dimension in the Circle of Integral Well-being (CBI in Spanish) through the argumentation of the educational approach of integral prevention. The research approach is qualitative with content-analysis design. Three steps were carried out in the methodology: first, the empirical data were collected with different techniques; subsequently, the data were organized for the understanding and construction of analysis categories and, finally, the data were analyzed with a comparative method. Among the main results, a new dimension is incorporated in the educational approach of integral prevention “circle of integral well-being” and the theoretical argumentation of the cultural dimension. In addition, the importance of rethinking and reflecting on the theoretical and methodological bases of the discipline is highlighted in the face of the new challenges that arise.